2019
DOI: 10.1609/aaai.v33i01.33014295
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Manytasking Optimization Based on Symbiosis in Biocoenosis

Abstract: Evolutionary multitasking is a significant emerging search paradigm that utilizes evolutionary algorithms to concurrently optimize multiple tasks. The multi-factorial evolutionary algorithm renders an effectual realization of evolutionary multitasking on two or three tasks. However, there remains room for improvement on the performance and capability of evolutionary multitasking. Beyond three tasks, this paper proposes a novel framework, called the symbiosis in biocoenosis optimization (SBO), to address evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In MTMSO, each population is responsible for one unique task, and knowledge transfer across these population is implemented via the probabilistic crossover on these population's personal bests. In addition, there are many other EMTO solvers proposed in recent years [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In MTMSO, each population is responsible for one unique task, and knowledge transfer across these population is implemented via the probabilistic crossover on these population's personal bests. In addition, there are many other EMTO solvers proposed in recent years [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Equipped with the capability of latent genetic transfer, Evolutionary Multitasking can resolve many optimization problems simultaneously by enabling the knowledge transfer among different problems through the unified chromosome representation. In control of the synergies of searching space for varying optimization tasks (Gupta et al, 2016a,b;Da et al, 2018;Zhou et al, 2018), Evolutionary Multitasking, which can be easily employed on existing population-based algorithm (Feng et al, 2017;Chen et al, 2018;Liu et al, 2018;Zhong et al, 2019), have shown promising results on a vast number of cases in multi-objective optimization (Gupta et al, 2016c;Feng et al, 2018), symbolic regression (Zhong et al, 2018a), capacitated vehicle routing problems (Zhou et al, 2016), expensive optimization tasks (Min et al, 2017), and can be extended to a large scale version (Chen et al, 2019;Liaw and Ting, 2019) to enable some more scalable applications in the future. The methodology of Evolutionary Multitasking paradigm naturally fits the multi-classification problem, by treating each binary classification problem as an optimization task within certain function evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on many-tasking have been carried out in the domain singleobjective optimization [96,97]. Along similar lines, we extend our current experimental study to more than two multi-objective tasks.…”
Section: Study With More Than Two Tasksmentioning
confidence: 64%
“…Since the conceptualization of evolutionary multitasking, various algorithmic realizations have come to the fore [9,12,21,22,30,[51][52][53][54][55][56][57]. Notably, the crossover-based multifactorial evolutionary algorithms (i.e., MFEA and MO-MFEA) [21,22] have so far been the most prominent ones.…”
Section: The Multifactorial Evolutionary Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation